Asymmetric aminocatalysis: a modern strategy for molecules, challenges and life - Pesciaioli, Fabio <1982> (Alma Mater Studiorum - Università di Bologna, 2011)

(untitled)
The studies conducted during my Phd thesis were focused on two different directions: